2020
DOI: 10.3390/su12219075
|View full text |Cite
|
Sign up to set email alerts
|

CSR in Non-Large Public Interest Entities: Corporate Talk vs. Actions

Abstract: Smaller companies’ understanding of and attitude toward corporate social responsibility (CSR), both in terms of actions and disclosure, is distinct from that of other organizations, including large public interest entities (PIEs) that dominate the existing literature in the field. In this study, we examine the interdependencies between non-large PIEs’ CSR practices and disclosures with the use of the organizational hypocrisy concept as a theoretical lens. Our sample consists of 111 companies operating in Polan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
1
1
0
1
Order By: Relevance
“…Almost half of the Polish companies provided disclosures relating to local communities (47%) and environmental impact (45%) (Table 4). This finding is consistent with the results of Krasodomska and Godawska (2020), who identified community involvement and development, labor practices and the environment as most frequently mentioned in the disclosures of non-public entities operating in Poland. However, when we compared the disclosure indices, the extent of environment-related disclosures is the highest.…”
Section: Descriptive Resultssupporting
confidence: 91%
“…Almost half of the Polish companies provided disclosures relating to local communities (47%) and environmental impact (45%) (Table 4). This finding is consistent with the results of Krasodomska and Godawska (2020), who identified community involvement and development, labor practices and the environment as most frequently mentioned in the disclosures of non-public entities operating in Poland. However, when we compared the disclosure indices, the extent of environment-related disclosures is the highest.…”
Section: Descriptive Resultssupporting
confidence: 91%
“…On the other hand, research has been carried out in the case of companies that are not of public interest. Krasodomska and Godawska [ 37 ] studied the behavior of a sample of non-public entities from Poland by analyzing the content of these companies’ websites. The results showed that CSR practices were briefly presented on websites, and there were mostly governance issues and environmental protection actions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…La pandemia de la Covid-19 ha transformado la vida cotidiana, la economía global y el ámbito educativo. La educación, como uno de los pilares fundamentales, se ha visto afectada por las medidas de distanciamiento social y las restricciones impuestas para contener la propagación del virus (Aretio, 2020;Francesc, 2020;Kohls-Santos, 2021;Krasodomska & Godawska, 2021).…”
Section: Introductionunclassified